EEG utilization in Canadian intensive care units: A multicentre prospective observational study. (December 2016) - Park, Andrea; Chapman, Martin; McCredie, Victoria A.; Debicki, Derek; Gofton, Teneille; Norton, Loretta; Boyd, J. Gordon
Highlights: EEG monitoring is indicated for approximately one-third of critically ill patients. Only 37% of patients with indications for EEGs had EEGs performed. Continuous EEG was rarely used. Abstract: Purpose: We have previously shown that electroencephalography (EEG) may be an underutilized monitoring modality in a single general medical-surgical ICU, that does not have a specific neurocritical care consultation service or neurocritical care unit. The present study was designed to describe the pattern of EEG utilization across 3 academic ICUs in Ontario, Canada that use different models of neurocritical care. Method: In this prospective multicentre observational study, ICU patients were screened weekly for 6 non-consecutive weeks to determine if they met the ESICM's recommendations or suggestions for EEG monitoring. If EEGs were performed, the results were recorded. Three models of neurocritical care provision were examined in 3 academic tertiary ICUs. Site 1 is an intensivist-led, medical-surgical ICU with no specific neurocritical care consultation service. The second site is also an intensivist led medical-surgical ICU, but with a formal neurocritical care consultation service. The third site is a virtual neurological and neurotrauma ICU within a medical-surgical ICU, staffed by rotating neurointensivists and general intensivists. Results: Of the 375 patients who were screened, 127 patients (34%) met at least one ESICM indication for EEG monitoring. Among the 127 patients, 46 patients (37%) had an EEG performed. Site 1 had the highest proportion of EEGs performed. The most common indication for EEG monitoring was for patients with unexplained altered level of consciousness, in the absence of primary brain injury. For the EEGs performed per ESICM indication, the majority of epileptiform abnormalities were found in patients admitted with status epilepticus. Conclusions: EEG may be underutilized in Canadian ICUs. The impact on patient management and outcomes are unknown.